Drosophila as a model for studying cystic fibrosis pathophysiology of the gastrointestinal system - Kim, Kevin (Proc Natl Acad Sci U S A, 2020)
Cystic fibrosis (CF) is a recessive disease caused by mutations in the CF transmembrane conductance regulator (CFTR) gene. The most common symptoms include progressive lung disease and chronic digestive conditions. CF is the first human genetic disease to benefit from having five different species of animal models. Despite the phenotypic differences among the animal models and human CF, these models have provided invaluable insight into understanding disease mechanisms at the organ-system level. Here, we identify a member of the ABCC4 family, CG5789, that has the structural and functional properties expected for encoding the Drosophila equivalent of human CFTR, and thus refer to it as Drosophila CFTR (Dmel\CFTR). We show that knockdown of Dmel\CFTR in the adult intestine disrupts osmotic homeostasis and displays CF-like phenotypes that lead to intestinal stem cell hyperplasia. We also show that expression of wild-type human CFTR, but not mutant variants of CFTR that prevent plasma membrane expression, rescues the mutant phenotypes of Dmel\CFTR. Furthermore, we performed RNA sequencing (RNA-Seq)-based transcriptomic analysis using Dmel\CFTR fly intestine and identified a mucin gene, Muc68D, which is required for proper intestinal barrier protection. Altogether, our findings suggest that Drosophila can be a powerful model organism for studying CF pathophysiology.